Strategi Bersaing PT. Perusahaan Gas Negara (Persero) Tbk SBU Distribusi Wilayah I - Jomaren Tuah Saragih; Eko Suryadi (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2014)
The purpose of thi s research is to analyze competitive strategy implemented by PT Perusahaan Gas Negara(Perser o)  Tbk SBU  Dist ribusi  Wilayah I  to  face competit ion  in downstr eam  natural  gas industry.   Descript ivequalitat ive analysis method  is used by carrying  out SWOT  and V alue  Chain Analysis.   SWOT analysis  is usedto  ident ify  and evaluate st r ength, weakness,  opportunity, and threat  of the company,  whereas  the importantfactors  and  their  r elevance  to  the  futur e  ar e  ident ified  by  V alue  Chain Analysi s.The  r esults  show  that  SBUWilayah  I  uses  best  price  strategy  and  gives  value  added  cutomer  service  by  maximizing  the  use  of  technologyto  create  sustainable  competitive  advantage.